Some Subsets of Bitopological Spaces - R. Rajalakshmi; C. Carpintero; N. Rajesh; E. Rosas (International Journal of Analysis and Applications, 2023)
In this paper, we introduce the notions of minimal u-ω-closed sets, maximal u-ω-open sets, u-ω-paraopen sets, u-ω-paraclosed sets, u-ω-mean open sets and u-ω-mean closed sets in bitopological spaces and obtain several characterizations and some of its properties.